Population genetic structure of a bamboo hybrid (×Gigantocalamus malpenensis) in Perak, Malaysia, and implications for silviculture - Kong, Huei Huei (2023)
The most economically important wild bamboo species in Peninsular Malaysia, Gigantochloa scortechinii Gamble (Buluh Semantan), has lately been found to hybridise with another common bamboo species, Dendrocalamus pendulus Ridl. (Buluh Akar), in the locations where both species co-exist. Their hybrid species (×Gigantocalamus malpenensis K.M. Wong) appears to have large and straight culms like those of G. scortechinii and the flexural strength that is similar to D. pendulus. These characters make it a good candidate for various applications in the construction industry. In this study, a new locality (Sungai Siput, Perak) for ×G. malpenensis was reported. Molecular studies were based on the DNA sequence data of two nuclear DNA markers, Granule Bound Starch Synthase I (GBSSI) and cellulase-like protein 1 (PvCel1) genes; and four Inter-simple Sequence Repeats (ISSR) markers, Wolfe899, UBC 810, UBC 857, and UBC 864. Network analysis, Bayesian phylogenetic analysis, population STRUCTURE analysis, population pairwise FST analysis, and Principal Coordinate Analysis (PCoA) were used to infer the genetic differentiation and population structures of the hybrid and its parental populations. The hybrid population in Sungai Siput was suggested to consist of only F1 generation. No significant genetic differentiation was detected between the hybridising and non-hybridising populations of G. scortechinii, suggesting that the population iii structure of the parental populations may not be adversely affected by the occurrence of the new hybrid population. The hybrid population demonstrated a considerably high degree of genetic heterozygosity, implying its non-uniformity in morphological and physiological properties among the hybrid individuals. Hence, there will be various choices for clone selection in silviculture. It was anticipated that more hybrid populations will emerge in the future as driven by environmental factors (e.g., anthropogenic disturbance). The promising side of it is that supply of this hybrid bamboo species from the wild would be continuous.